High-rate lead-acid battery negative electrode material and preparation method thereof

By using modified acetylene black, zinc oxide, indium oxide and other materials in lead-acid batteries, the negative electrode materials of high-ratio lead-acid batteries are prepared, which solves the problems of low discharge rate and short life of lead-acid batteries, and significantly improves the electrochemistry of the batteries Performance and stability extend battery life.

CN119230764AActive Publication Date: 2024-12-31JIANGSU OLITER ENERGY TECH CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411534298.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-31
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing lead-acid batteries have problems with low discharge rate, short life, hydrogen evolution and irreversible sulfateization, which limits their use range.

Method used

Using modified acetylene black, zinc oxide, indium oxide and other materials, high-rate lead-acid battery negative electrode materials are prepared through ultrasonic dispersion and grinding steps, improving the electrochemical performance of the electrode, inhibiting hydrogen evolution and sulfateization, and improving cycle life and safety. performance.

Benefits of technology

It effectively improves the discharge capacity, cycle life and stability of the battery, reduces polarization and hydrogen evolution problems, and enhances the durability and charge and discharge efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111181940000021
    Figure BDA0005111181940000021
  • Figure BDA0005111181940000031
    Figure BDA0005111181940000031
  • Figure BDA0005111181940000032
    Figure BDA0005111181940000032
Patent Text Reader

Abstract

The invention discloses a high-rate lead-acid battery negative electrode material and a preparation method thereof, and belongs to the technical field of electrochemistry. Adding a lead-containing compound, the modified acetylene black, deionized water and ethanol into a flask, and performing ultrasonic treatment, filtering and drying to obtain a composite material; and pouring a premix 2 obtained by mixing polyvinyl alcohol, sodium polystyrenesulfonate and deionized water into a premix 1 obtained by mixing and grinding lead sulfate, conductive graphite, the composite material and barium sulfate, stirring, grinding, coating, compacting and drying to obtain the negative electrode material. Zinc oxide and indium oxide firmly exist in the modified acetylene black, and the modified acetylene black and the lead-containing compound have high dispersity in the negative electrode material, so that the negative electrode material can improve the distribution of conductive graphite and is more beneficial to ion and electron transmission; hydrogen evolution can be inhibited, the hydrogen evolution overpotential is improved, and the charge-discharge acceptance and efficiency of the electrode are improved; the electrode internal resistance and polarization can be reduced, the sulfation phenomenon of the negative electrode is relieved, the cycle performance of the electrode is improved, and the service life of the electrode is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology, and in particular, relates to a high-rate lead-acid battery negative electrode material and a preparation method thereof. Background Art

[0002] Lead-acid batteries are highly safe, inexpensive and high-quality industrial products. Lead-acid batteries are widely used as car starting power supplies, electric two-wheeled vehicle power supplies, uninterruptible backup power supplies, diesel submarine underwater navigation power supplies, communication industry backup power supplies, etc., and have a wide range of applications. In recent years, with the development of renewable energy, lead-acid batteries have also been used in large-scale energy storage power supplies.

[0003] However, current lead-acid batteries generally have problems such as low discharge rate or short life under high-rate discharge conditions. There are also problems such as hydrogen evolution and irreversible sulfation, which limit the use of lead-acid batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-rate lead-acid battery negative electrode material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A high-rate lead-acid battery negative electrode material and a preparation method thereof, comprising the following steps:

[0007] (1) adding a lead-containing compound, modified acetylene black, deionized water and ethanol into a dry single-necked flask, ultrasonically dispersing for 1 h, then filtering, and drying at 80° C. for 12 h to obtain a composite material;

[0008] (2) Lead sulfate, conductive graphite, composite material and barium sulfate are mixed and ground evenly to obtain premix 1; polyvinyl alcohol, sodium polystyrene sulfonate and deionized water are added to a beaker and mixed evenly to obtain premix 2; premix 2 is poured into premix 1, and stirring and grinding are continued to form a paste, which is coated on a lead-calcium alloy grid, and then compacted with an oil press, and finally dried at 70° C. for 24 hours to obtain a high-rate lead-acid battery negative electrode material.

[0009] Furthermore, the lead-containing compound in step (1) is one of lead, lead oxide and lead tetroxide.

[0010] Furthermore, the modified acetylene black in step (1) is prepared by the following steps:

[0011] S1. Under nitrogen protection, benzimidazole-5-carboxylic acid, EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), NHS (N-hydroxysuccinimide) and DMF (N,N-dimethylformamide) were added to a dry three-necked flask, stirred and dissolved, and then heated to 50°C, and then D-glucosamine was slowly added. The reaction was kept warm for 6 hours. After the reaction was completed, it was cooled to room temperature and distilled under reduced pressure. Column chromatography was purified (the eluent was a mixed solvent of chloroform and acetone, and the volume ratio of chloroform and acetone was 7:3). Distilled under reduced pressure to obtain intermediate 1; the amount ratio of D-glucosamine, benzimidazole-5-carboxylic acid, EDC, NHS and DMF was 19.6g:16.2g:3.8g:2.3g:200mL;

[0012] The molar ratio of D-glucose amine to benzimidazole-5-carboxylic acid is controlled to be 1.05-1.1:1, and the -COOH of benzimidazole-5-carboxylic acid and the -NH 2 Under the action of EDC and NHS, an amidation reaction occurs. The reaction equation is shown below:

[0013]

[0014] S2, add acetylene black and concentrated sulfuric acid to a dry three-necked flask, stir and heat to 80 ° C, and continue to reflux for 12h, stop stirring and cool to room temperature, filter, wash with deionized water, and vacuum dry at 110 ° C for 6h to obtain pretreated acetylene black; mix the pretreated acetylene black, 10% sodium hydroxide solution and chloroform, stir and heat to 60 ° C, then slowly add epichlorohydrin, continue to keep warm at 60 ° C for 6h, after the reaction is completed, rotary evaporate, wash with deionized water 3 times, and then dry at 110 ° C for 6h to obtain intermediate 2; the amount ratio of acetylene black and concentrated sulfuric acid is 10g:330mL; the amount ratio of pretreated acetylene black and epichlorohydrin is 7.7g:10mL;

[0015]

[0016] S3, under nitrogen protection, add intermediate 2, triethylamine and DMF into a dry three-necked flask, stir and heat to 80°C, then slowly add intermediate 1, keep warm for 6 hours after the addition is complete, distill under reduced pressure after the reaction is complete, wash with deionized water 3 times, and then dry at 110°C for 6 hours to obtain intermediate 3; the amount ratio of intermediate 1, intermediate 2, triethylamine and DMF is 43.7g:14g:20.5mL:220mL;

[0017]

[0018] S4. Add intermediate 3 and deionized water into a beaker and perform ultrasonic treatment for 30 minutes to fully disperse intermediate 3; then add the mixed powder of zinc oxide and indium oxide, continue ultrasonic treatment for 1 hour, then filter and vacuum dry at 110°C for 12 hours to obtain modified acetylene black; the dosage ratio of intermediate 3, zinc oxide, indium oxide and deionized water is 30g:0.015g:0.015g:250mL.

[0019] The role of indium oxide added to the negative electrode material of lead-acid batteries is to improve the performance of the battery, including increasing the discharge capacity, extending the cycle life, and inhibiting the negative electrode sulfation and hydrogen evolution problems; the role of zinc oxide in lead-acid batteries is mainly reflected in improving the battery's cycle life, safety performance, and enhancing the battery's stability and durability by improving the sulfation phenomenon of the negative plate.

[0020] Since zinc oxide and indium oxide both contain abundant hydroxyl groups on their surfaces, zinc oxide and indium oxide can interact with the hydroxyl groups on the surface of intermediate 3 through hydrogen bonds. In addition, the nitrogen atom in the benzimidazole structure on intermediate 3 contains lone pairs of electrons, which have strong coordination ability and are easy to form complexes with zinc oxide and indium oxide. The complexes formed have a good rigid planar structure and abundant π electrons, as well as an excellent electron delocalization environment. Moreover, the π-π stacking effect of the aromatic ring in the benzimidazole structure on intermediate 3 makes the complexes more stable. Thus, zinc oxide and indium oxide can be firmly present in the modified acetylene black and work synergistically to improve the discharge capacity, extend the cycle life, inhibit the negative electrode sulfation and hydrogen evolution problems, and enhance the stability and durability of the battery.

[0021] In addition, the surface of the modified acetylene black contains abundant hydroxyl groups, which can generate hydrogen bond interactions with the hydroxyl groups in deionized water and ethanol, so that the modified acetylene black can be more fully dispersed in the system, and the lead-containing compound can be more evenly loaded on the surface of the acetylene black. Furthermore, the composite material prepared in step (1) of the present invention can effectively improve the electrochemical performance of the electrode, and reduce the hydrogen evolution problem generated during the charging process at a low rate, improve the charge and discharge efficiency, and can bear part of the discharge current at a high rate, which can alleviate the accumulation of lead sulfate and reduce polarization, and at the same time improve the cycle life and safety performance of the battery, and enhance the stability and durability of the battery by improving the sulfation phenomenon of the negative plate.

[0022] Furthermore, the dosage ratio of the lead-containing compound, modified acetylene black, deionized water and ethanol in step (1) is (0.02-0.06) g: 0.12 g: 50 mL: 50 mL.

[0023] Furthermore, the mass ratio of lead sulfate, conductive graphite, composite material, barium sulfate, polyvinyl alcohol and sodium polystyrene sulfonate in step (2) is 1:(0.015-0.03):(0.005-0.015):0.02:0.005:0.002.

[0024] A high-rate lead-acid battery negative electrode material is prepared according to the above-mentioned method for preparing a high-rate lead-acid battery negative electrode material.

[0025] The beneficial effects of the present invention are as follows: zinc oxide and indium oxide are firmly present in the modified acetylene black through chemical reaction, and play a synergistic role. In addition, the modified acetylene black and the lead-containing compound have high dispersion in the negative electrode material, so the negative electrode material of the present invention can improve the distribution of conductive graphite, which is more conducive to ion and electron transmission; at the same time, it can inhibit hydrogen evolution, increase hydrogen evolution overpotential, and improve the charge and discharge acceptance and efficiency of the electrode; it can also reduce the internal resistance and polarization of the electrode, alleviate the sulfation phenomenon of the negative electrode, improve the cycle performance of the electrode, and extend the life of the electrode. Therefore, the finished battery made by using the negative electrode material of the present invention has excellent electrochemical performance. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] Preparation of modified acetylene black, the specific steps are as follows:

[0029] S1. Under nitrogen protection, 16.2 g of benzimidazole-5-carboxylic acid, 3.8 g of EDC, 2.3 g of NHS and 200 mL of DMF were added to a 500 mL dry three-necked flask, stirred and dissolved, and then the temperature was raised to 50°C. Then, 19.6 g of D-glucosamine was slowly added, and the reaction was kept warm for 6 h. After the reaction was completed, it was cooled to room temperature, distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solvent of chloroform and acetone, and the volume ratio of chloroform and acetone was 7:3), and distilled under reduced pressure to obtain intermediate 1;

[0030] S2, 10g acetylene black, 330mL concentrated sulfuric acid were added to a 500mL dry three-necked flask, stirred and heated to 80°C, and then refluxed for 12h, stopped stirring and cooled to room temperature, filtered, washed with deionized water, and vacuum dried at 110°C for 6h to obtain pretreated acetylene black; 7.7g pretreated acetylene black, 50mL of 10% sodium hydroxide solution and 100mL chloroform were mixed evenly, stirred and heated to 60°C, and then 10mL epichlorohydrin was slowly added, and the reaction was continued at 60°C for 6h. After the reaction was completed, the mixture was evaporated, washed with deionized water 3 times, and then dried at 110°C for 6h to obtain intermediate 2;

[0031] S3, under nitrogen protection, add 14g of intermediate 2, 20.5mL of triethylamine and 220mL of DMF into a 500mL dry three-necked flask, stir and heat to 80°C, then slowly add 43.7g of intermediate 1, keep warm for 6h after the addition is complete, distill under reduced pressure after the reaction is complete, wash with deionized water 3 times, and then dry at 110°C for 6h to obtain intermediate 3;

[0032] S4. Add 30 g of intermediate 3 and 250 mL of deionized water into a beaker, and perform ultrasonic treatment for 30 min to fully disperse the intermediate 3; then add a mixed powder of 0.015 g of zinc oxide and 0.015 g of indium oxide, continue ultrasonic treatment for 1 h, then filter, and vacuum dry at 110° C. for 12 h to obtain modified acetylene black.

[0033] Example 2

[0034] The specific steps for preparing the negative electrode material of a high-rate lead-acid battery are as follows:

[0035] (1) 0.06 g of lead tetroxide, 0.12 g of the modified acetylene black prepared in Example 1, 50 mL of deionized water and 50 mL of ethanol were added to a 250 mL dry single-necked flask, ultrasonically dispersed for 1 h, then filtered, and dried at 80 ° C for 12 h to obtain a composite material;

[0036] (2) Lead sulfate, conductive graphite, composite material and barium sulfate are mixed and ground evenly to obtain premix 1; polyvinyl alcohol, sodium polystyrene sulfonate and deionized water are added into a beaker and mixed evenly to obtain premix 2, wherein the mass ratio of lead sulfate, conductive graphite, composite material, barium sulfate, polyvinyl alcohol and sodium polystyrene sulfonate is 1:0.03:0.015:0.02:0.005:0.002; premix 2 is poured into premix 1, and stirring and grinding are continued to form a paste, which is applied on a lead-calcium alloy grid, compacted by a hydraulic press, and finally dried at 70° C. for 24 hours to obtain a high-rate lead-acid battery negative electrode material.

[0037] Example 3

[0038] The specific steps for preparing the negative electrode material of a high-rate lead-acid battery are as follows:

[0039] (1) 0.04 g of lead oxide, 0.12 g of the modified acetylene black prepared in Example 1, 50 mL of deionized water and 50 mL of ethanol were added to a 250 mL dry single-necked flask, ultrasonically dispersed for 1 h, then filtered, and dried at 80 ° C for 12 h to obtain a composite material;

[0040] (2) Lead sulfate, conductive graphite, composite material and barium sulfate are mixed and ground evenly to obtain premix 1; polyvinyl alcohol, sodium polystyrene sulfonate and deionized water are added into a beaker and mixed evenly to obtain premix 2, wherein the mass ratio of lead sulfate, conductive graphite, composite material, barium sulfate, polyvinyl alcohol and sodium polystyrene sulfonate is 1:0.025:0.01:0.02:0.005:0.002; premix 2 is poured into premix 1, and stirring and grinding are continued to form a paste, which is coated on a lead-calcium alloy grid, compacted by a hydraulic press, and finally dried at 70° C. for 24 hours to obtain a high-rate lead-acid battery negative electrode material.

[0041] Example 4

[0042] The specific steps for preparing the negative electrode material of a high-rate lead-acid battery are as follows:

[0043] (1) 0.02 g of lead, 0.12 g of the modified acetylene black prepared in Example 1, 50 mL of deionized water and 50 mL of ethanol were added to a 250 mL dry single-necked flask, ultrasonically dispersed for 1 h, then filtered, and dried at 80 ° C. for 12 h to obtain a composite material;

[0044] (2) Lead sulfate, conductive graphite, composite material and barium sulfate are mixed and ground evenly to obtain premix 1; polyvinyl alcohol, sodium polystyrene sulfonate and deionized water are added into a beaker and mixed evenly to obtain premix 2, wherein the mass ratio of lead sulfate, conductive graphite, composite material, barium sulfate, polyvinyl alcohol and sodium polystyrene sulfonate is 1:0.015:0.005:0.02:0.005:0.002; premix 2 is poured into premix 1, and stirring and grinding are continued to form a paste, which is applied on a lead-calcium alloy grid, compacted by a hydraulic press, and finally dried at 70° C. for 24 hours to obtain a high-rate lead-acid battery negative electrode material.

[0045] Comparative Example 1

[0046] The specific steps for preparing the negative electrode material of lead-acid battery are as follows:

[0047] The remaining steps remain unchanged, except that the modified acetylene black in step (1) of Example 2 is replaced by acetylene black that has not been treated in any way, to prepare a negative electrode material for a lead-acid battery.

[0048] Comparative Example 2

[0049] The specific steps for preparing the negative electrode material of lead-acid battery are as follows:

[0050] The remaining steps remain unchanged, except that step (1) of Example 2 is removed, and the composite material in step (2) is removed to prepare a negative electrode material for a lead-acid battery.

[0051] Performance Testing

[0052] The lead-acid battery negative electrode materials prepared in Examples 2-4 and Comparative Examples 1-2 were prepared into lead-acid batteries, and the following tests were performed:

[0053] Service life test: The lead-acid batteries of Examples 2-4 and Comparative Examples 1-2 were tested for the number of cycles. If the number of cycles was higher than 700, it was qualified, otherwise it was unqualified. Stability test: The discharge time of the lead-acid batteries of Examples 2-4 and Comparative Examples 1-2 was tested at 300 cycles. If it was higher than 150 minutes, it was qualified, otherwise it was unqualified. The test results are shown in the following table:

[0054]

[0055]

[0056] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0057] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-rate lead-acid battery negative electrode material and a preparation method thereof, characterized in that: The following steps are involved: (1) adding a lead-containing compound, modified acetylene black, deionized water and ethanol into a flask, ultrasonically dispersing for 1 h, filtering and drying to obtain a composite material; (2) Lead sulfate, conductive graphite, composite material, and barium sulfate are mixed and ground to obtain premix 1; polyvinyl alcohol, sodium polystyrene sulfonate, and deionized water are mixed to obtain premix 2; premix 2 is poured into premix 1, stirred, ground, coated on a lead-calcium alloy grid, compacted with an oil press, and dried to obtain a high-rate lead-acid battery negative electrode material; Wherein, the modified acetylene black in step (1) is prepared by the following steps: S1. Benzimidazole-5-carboxylic acid, EDC, NHS and DMF were added to a flask under nitrogen protection, heated to 50°C with stirring, and D-glucosamine was added. The reaction was continued for 6 hours, cooled, distilled under reduced pressure, purified by column chromatography, and distilled under reduced pressure to obtain intermediate 1. S2, add acetylene black and concentrated sulfuric acid into a flask, reflux at 80°C for 12h, cool, filter, wash, and dry to obtain pretreated acetylene black; stir the pretreated acetylene black, 10% sodium hydroxide solution and chloroform, heat to 60°C, add epichlorohydrin, react for 6h, rotary evaporate, wash, and dry to obtain intermediate 2; S3, under nitrogen protection, add intermediate 2, triethylamine and DMF into a flask, stir and heat to 80°C, add intermediate 1, react for 6h, distill under reduced pressure, wash and dry to obtain intermediate 3; S4. Add intermediate 3 and deionized water into a beaker, sonicate for 30 min, add mixed powder of zinc oxide and indium oxide, sonicate for 1 h, filter, and dry to obtain modified acetylene black.

2. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The usage ratio of D-glucosamine, benzimidazole-5-carboxylic acid, EDC, NHS and DMF in step S1 is 19.6 g:16.2 g:3.8 g:2.3 g:200 mL.

3. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The usage ratio of acetylene black and concentrated sulfuric acid in step S2 is 10g:330mL; the usage ratio of pretreated acetylene black and epichlorohydrin is 7.7g:10mL.

4. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The usage ratio of intermediate 1, intermediate 2, triethylamine and DMF in step S3 is 43.7 g:14 g:20.5 mL:220 mL.

5. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The usage ratio of intermediate 3, zinc oxide, indium oxide and deionized water in step S4 is 30 g: 0.015 g: 0.015 g: 250 mL.

6. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The lead-containing compound in step (1) is one of lead, lead oxide and lead tetroxide.

7. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The amount ratio of the lead-containing compound, modified acetylene black, deionized water and ethanol in step (1) is (0.02-0.06) g: 0.12 g: 50 mL: 50 mL.

8. A high-rate lead-acid battery negative electrode material and a preparation method thereof according to claim 1, characterized in that: The mass ratio of lead sulfate, conductive graphite, composite material, barium sulfate, polyvinyl alcohol and sodium polystyrene sulfonate in step (2) is 1:(0.015-0.03):(0.005-0.015):0.02:0.005:0.

002.

9. A high-rate lead-acid battery negative electrode material, characterized in that: It is prepared according to the method for preparing a high-rate lead-acid battery negative electrode material according to any one of claims 1-8.

Citation Information

Patent Citations

  • Preparation method for lead-carbon composite material of lead acid battery and composite negative plate

    CN104393250A

  • Composite electrode material improving current discharge performance and preparation method thereof

    CN104851612A

  • Lead storage battery negative electrode lead paste and preparation method thereof

    CN107331834A

  • Negative electrode material of lead-carbon battery with high circulation times and preparation method

    CN107732162A

  • High-performance lead-carbon battery negative electrode lead paste formula and preparation method thereof

    CN113764627A